Probing magnetic-proximity-effect enlarged valley splitting in monolayer WSe2 by photoluminescence - Zou, Chenji (2020)
Possessing a valley degree of freedom and potential in information processing by manipulating valley features (such as valley splitting), group-VI monolayer transition metal dichalcogenides have attracted enormous interest. This valley splitting can be measured based on the difference between the peak energies of σ+ and σ− polarized emissions for excitons or trions in direct band gap monolayer transition metal dichalcogenides under perpendicular magnetic fields. In this work, a well-prepared heterostructure is formed by transferring exfoliated WSe2 onto a EuS substrate. Circular-polarization-resolved photoluminescence spectroscopy, one of the most facile and intuitive methods, is used to probe the difference of the gap energy in two valleys under an applied out-of-plane external magnetic field. Our results indicate that valley splitting can be enhanced when using a EuS substrate, as compared to a SiO2/Si substrate. The enhanced valley splitting of the WSe2/EuS heterostructure can be understood as a result of an interfacial magnetic exchange field originating from the magnetic proximity effect. The value of this magnetic exchange field, based on our estimation, is approximately 9 T. Our findings will stimulate further studies on the magnetic exchange field at the interface of similar heterostructures.